Expression and function of TNF-family proteins and receptors in human osteoblasts. - Bu, R; Borysenko, C; Li, Y; Cao, L; Sabokbar, A; Blair, H (2003)
We studied how tumor necrosis-factor (TNF)-family proteins interact with osteoblasts to resolve several controversial points. We measured expression of TNFs, TNF-receptors, and nonsignaling (decoy) TNF receptors in human osteoblasts derived from mesenchymal stem cells and in MG63 human osteosarcoma cells using unamplified mRNA screening, with secondary Western or PCR analysis where indicated, and studied the effects of TNFs on osteoblasts in cell culture. Expression of TNFs and receptors was similar in MG63 cells and osteoblasts. TNF-R1 (p55), TRAIL receptor 1 and 2 (DR4 and 5), and Fas were expressed; RANK was undetectable. TNF-family ligands RANKL, TRAIL, and TNFalpha were expressed, but mRNAs were typically at low levels relative to receptors, suggesting that osteoblastic TNF signals, including RANKL, require specific stimuli. Flow cytometry of MG63 cells confirmed TNFalpha receptors and identified subpopulations with high surface-bound TNFalpha. Decoy receptors expressed included a novel soluble form of TNFRSF25 (formerly DR3 or Apo3), implicated in rheumatoid-arthritis linkage studies, as well as osteoprotegerin, a well-characterized osteoblast protein that binds TRAIL and RANKL, and DcR2, which binds TRAIL. Osteoblast apoptosis was studied using terminal deoxynucleotidyl transferase labeling and annexin V binding. MG63 cells were resistant to apoptosis by exogenous TNFalpha except when grown in media promoting osteoblast-like growth or matrix nodules. However, in media supporting osteoblast-like phenotype, apoptosis was induced by anti-Fas or TNF, in contrast to other studies with human osteoblasts. TRAIL caused cell retraction, supporting functional TRAIL response in cell differentiation, but did not cause apoptosis. We conclude that human osteoblasts have functional receptors for FasL, TNFalpha, TRAIL, but not RANKL, and that osteoblasts are protected by multiple nonsignaling TNF receptors against destruction by TNF-family proteins under conditions favoring cell growth.